Seed banks need investors - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Delegates at a recent United Nations Food and Agriculture Organization (FAO) conference in Leipzig agreed a 50-pageGlobal Plan of Action for the Conservation and Utilization of Plant Genetic Resources for Food and Agriculture. The delegatespromised...